The relationship between fatalism, depression and adherence to medication and health behaviors in coronary heart disease patients - Tan, Oliver Ruiwen (2018)
Recent research suggests that fatalism may be related to adherence to medication and recommended health behaviors in chronic illnesses such as Type-2 diabetes, but the relationship remains poorly explored in coronary heart disease (CHD). Fatalism may decrease medication adherence and specific adherence through its association with higher depressive symptoms. The current study aims to investigate the effect of fatalism on medication adherence in a sample of CHD patients by a) examining whether depression mediates the association between fatalism and adherence, and b) whether the effect of fatalism is moderated by the severity of depressive symptoms. A total of 136 patients with CHD were recruited from a cardiac rehabilitation programme at the Singapore Heart Foundation. Participants completed questionnaires measuring medication non-adherence, specific adherence, depression and fatalistic beliefs. Findings suggest that higher fatalism was associated with higher medication non-adherence, and the effect was mediated by depression. A marginal association was also found between higher fatalism and lower specific adherence to recommended health behaviors for CHD. This study highlights the importance of cultural beliefs on depression and adherence to treatment in CHD and suggests that further research into the constructs may be relevant in the Asian context. Early detection of depression and fatalistic health beliefs may also improve adherence and outcomes in cardiac rehabilitation.